THE CORRELATION BETWEEN LEARNING MOTIVATION AND READING COMPREHENSION ACHIEVEMENT AT THE X GRADE STUDENTS OF MAN 9 PONDOK KOPI EAST JAKARTA - Yuliasari, Ria; Virtianti, Rika; Yulianda, Annisa; Widyandary, Dirgahayunita (Jurnal Akrab Juara, 2020)
This research was conducted to measure whether there was any correlation or not between learning motivation and reading comprehension achievement. The population of this research was first grade students of MAN 9 Pondok Kopi East Jakarta that consisted of 99 students that were divided into three classes. The total sample was 40 students taken from the total population by simple random sampling. The method used in this research was survey which means that this is a quantitative research that uses questionnaire to a lot of objects. In this research, the writer gave questionnaires that consist of forty questions to those students in order to know their learning motivation. And then the writer gave multiple choice tests, to know their reading comprehension achievement. The result of the calculation of correlation coefficient Phi with 5% level of significant from the degree of freedom (df) = N is 3, 841 and the interpretation of the score 2 count and2 table indicated that2 count (32, 727) >2 table (3,841). Based on the result above, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It means there is correlation between learning motivation and reading comprehension achievement at the X grade students of MAN 9 Pondok Kopi East Jakarta.